Personalized virtual reality therapy for children with autism spectrum disorder - Belmaqrout, Ahlam; El Ghali, Btihal; Daoudi, Najima; Haqiq, Abdelhay (Institute of Advanced Engineering and Science, 2025)
The treatment of autism spectrum disorders (ASD) has often relied on broad therapeutic approaches that may not meet each individual's specific needs. This research highlights the importance of personalized therapy to address the unique sensory and emotional requirements of autistic children. We explore recent advances in therapeutic technologies, focusing on serious games and virtual reality (VR) as promising tools in this field. Our proposed solution is a VR application designed to provide a personalized, relaxing experience for children with autism. The application is tailored to accommodate individual preferences and sensory sensitivities, adjusting visual and auditory stimuli to reduce sensory overload and promote emotional regulation. This personalized approach aims to help children manage anxiety and stress more effectively.